Application of Benthic Fauna as Bioindicators for Water Quality Assessment : A Case Study of Bang Ban Canal, Ayutthaya Province - To-orn, Natthakitt (Burapha Science Journal, 2024)
Background and Objectives : The objective of this study was to observe the benthic fauna diversity and application of the biotic indices, BMWPthai score (Biological Monitoring Working Party) and ASTPthai (Average Score Per Taxa) to assess the water quality of the Bang Ban canal, Ayutthaya Province. Methodology : Benthic samples were collected from four sampling stations throughout the canal course in June 2020 (dry season), July-August 2020 (early rainy season) and September 2020 (late rainy season), using an Ekman grab. Water depth, transparency, temperature, pH, dissolved oxygen, conductivity and total dissolved solids were recorded in situ at each station, and sediment samples were taken for grain size analysis and organic matter assessment in a laboratory. Main Results : A total of 19 species belonging to 17 genera, in 13 families of benthic fauna were found. The dominant macrofauna in the area, including aquatic oligochaetes families Tubificidae (Branchiura sp. and Tubifex sp.) and Naididae (Dero sp.), polychaetes families Nepthyidae (Nepthys sp.) and Nereididae (Namalycastis sp., Nereis sp. and Dendronereis sp.), gastropods family Viviparidae (Mekongia swainsoni brueri), bivalves family Corbiculidae (Corbicula sp.), crustacean family Palaemonidae (Macrobrachium sp.), and insect larvae family Chironomidae (Chironomus sp.) were discovered. According to the result of the biological indices, BMWPthai score and ASPTthai, Bang Ban canal indicated poor water quality depending on the standard criteria of surface water quality category 4 (poor water quality). Conclusions : The study concluded that the BMWPthai score and ASPTthai can be used to assess water quality, with relationships to the number of families, density, richness index, diversity index, and evenness index.